The Implication of Government Bias on the Resolution of Communal Conflict in Nigeria - Onwe, Hilary Nwachukwu; Awotayo, Olagoke Oluwafemi; Akinpelu, Afisu Oluwole; Adelekan, Akeem Tunde (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
The incidence of communal conflicts in Nigeria has been on the rise since the 1990s. these conflicts cut across all sections of the country, from the North to South. Interestingly, these conflicts are mostly anchored on disputes over land and the dichotomy between indigene and settlers. As one with the monopoly of force, the state, through the government is expected to be an effective arbiter but this has not been the case in terms of government intervention in communal conflict in the country. The reason for this is the perceived bias by the parties on government intervention. The implication of such perceived bias is that it is difficult to resolve such conflicts. This study argued that there are standard procedures that the government is expected to follow if its intervention will sail through. The study maintained that these procedures would help in building trust in government by the parties for a smooth resolution of communal conflict. Keywords: Conflict, conflict resolution, communal conflict, land, communal bias.